DNA analysis for the post genome-sequencing era - Kambara, Hideki (Rinsho byori. The Japanese journal of clinical pathology, 2002)
With the completion of the human genome sequencing, the new post genome-sequencing era has started. The major subjects are clarifying the function of genes to apply this information to medical as well as various industrial fields. Various DNA analysis methods and instruments for gene expression profiling as well as genetic diversity including SNPs typing are required and have been developed. Here, the history and technologies related to DNA analysis including the Wada project in the early 1980's, and the Human genome project from 1990 are described. Various new technologies have developed in this decade. They include a capillary gel array DNA sequencer, DNA chips, bead probe arrays, a new DNA sequencing method using pyrosequencing and an efficient SNP typing method by BAMPER.